1990
DOI: 10.1002/cne.902920209
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in the density and distribution of neurotensin‐like immunoreactive fibers in the mediodorsal nucleus of the thalamus in the rat

Abstract: A previous report (Inagaki et al., Brain Res. 260:143-146, '83) suggested that the peptide neurotensin is contained in neurons of the piriform cortex that project to the mediodorsal thalamic nucleus (MD) in young rats. To confirm this, we have studied the distribution of neurotensin-like immunoreactive (NTIR) fibers in MD during development, using three antisera directed at different parts of the neurotensin molecule (Emson et al., J. Neurochem. 38:992-999, '82). In adult rats, NTIR fibers in MD are sparse. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although no tracing study devoted specifically to the ventral endopiriform area appears to exist (Behan & Haberly, 1999), it nonetheless has been demonstrated that neurons in this area receive olfactory information via a substantial projection from the superficial layer of the piriform cortex (Luskin & Price, 1983) and convey this information to the mediodorsal and submedial thalamic nuclei (Price & Slotnick, 1983). A subpopulation of the mediodorsal‐projecting neurons utilize NT as a neurotransmitter (Inagaki et al ., 1983; Ray & Price, 1990). Whether these neurons also project to the VTA or whether the NT‐containing VTA‐projecting neurons constitute a different population of neurons remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although no tracing study devoted specifically to the ventral endopiriform area appears to exist (Behan & Haberly, 1999), it nonetheless has been demonstrated that neurons in this area receive olfactory information via a substantial projection from the superficial layer of the piriform cortex (Luskin & Price, 1983) and convey this information to the mediodorsal and submedial thalamic nuclei (Price & Slotnick, 1983). A subpopulation of the mediodorsal‐projecting neurons utilize NT as a neurotransmitter (Inagaki et al ., 1983; Ray & Price, 1990). Whether these neurons also project to the VTA or whether the NT‐containing VTA‐projecting neurons constitute a different population of neurons remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Modern studies have consistently demonstrated non-uniform LHb distributions of immunoreactivity against various neuropeptides, mainly due to peptidergic enrichments in a small-celled (Pert and Atweh, 1976; Iwahori, 1977) medial core (e.g., opiates – Pert and Atweh, 1976; Atweh and Kuhar, 1977; substance P – Cuello, 1978; vasopressin – Buijis, 1978; Sofroniew and Weindl, 1978; somatostatin - Vincent et al, 1985; neurotensin - Ray and Price, 1990). Aside from the peptides, LHb neurons are reported to be mainly glutamatergic, expressing either vesicular glutamate transporter 2 (Geisler et al, 2007; Brinschwitz et al, 2010) or vesicular glutamate transporter 3 (Herzog et al, 2004).…”
Section: Cytology and Subnucleimentioning
confidence: 99%
“…The evidence for this association, however, appears to be vague. A variety of investigations based on morphologic demonstrations of neuropeptides (e.g., neurotensin: Ray and Price, 1990;somatostatin: Vincent et al, 1985;vasopressin: Sofroniew and Weindl, 1978), metabolically activated neurons (Chastrette et al, 1991;Nagao et al, 1993;Wirtshafter et al, 1994), and neurons or fibers visualized subsequent to anterograde or retrograde axonal tracing (Pasquier et al, 1976;Skagerberg et al, 1984;Behzadi et al, 1990;Hazrati and Parent, 1991;Steininger et al, 1992) have yielded ample evidence for the heterogeneous composition of the LHb. Unfortunately, the localization of the activated or immunoreactive neurons with respect to the subnuclear compositions of the LHb cannot be appreciated.…”
Section: Cytoarchitecture and Connections Of The Lhbmentioning
confidence: 99%